2011
DOI: 10.1007/s10067-011-1838-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of BVAS in patients with microscopic polyangiitis in Japan

Abstract: The validity of the Birmingham Vasculitis Activity Score (BVAS) as an index of disease activity and a predictor of the prognosis and outcome in patients with MPA has not yet been established in Japan. We conducted a retrospective study of the data of 73 patients with MPA who were followed up for at least 2 years. We divided the patients into two groups according to the BVAS, namely, the high-BVAS group (≥16) and the low-BVAS group (<16), and compared the clinical characteristics. In addition, the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The previous retrospective study, which included 73 Japanese MPA patients, showed that a higher BVAS (over 16 points) was correlated with shorter survival time and higher mortality rate (14). In the present study, we were able to stratify patients at high risk of death and ESRD by BVAS.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The previous retrospective study, which included 73 Japanese MPA patients, showed that a higher BVAS (over 16 points) was correlated with shorter survival time and higher mortality rate (14). In the present study, we were able to stratify patients at high risk of death and ESRD by BVAS.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, BVAS has been recognized not only as an evaluation tool for disease activity but also as a prognostic factor for patient survival in vasculitides (6,(12)(13)(14). As of yet, however, BVAS has not been sufficiently established as a prognostic factor for MPO-ANCA-related nephritis.…”
mentioning
confidence: 99%
“…The BVAS is an activity index for AAV, scoring 56 symptoms/signs across nine organ systems encompassing the entire body [12,17]. BVAS has been reported to predict poor prognosis in patients with MPA [18][19][20]. A study involving 55 patients with MPA revealed that BVAS was a useful predictor of survival, with high BVAS scores, age > 60 years, and the presence of interstitial lung disease associated with adverse outcomes [19].…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 55 patients with MPA revealed that BVAS was a useful predictor of survival, with high BVAS scores, age > 60 years, and the presence of interstitial lung disease associated with adverse outcomes [19]. Similarly, a study focusing on 73 Japanese patients with MPA reported signi cantly shorter survival times and higher mortality rates in a group with BVAS scores ≥ 16 [20]. In line with previous research, our multicentre cohort study in Japan found a signi cant association between BVAS scores of 20 and poor life prognosis in patients with MPA.…”
Section: Discussionmentioning
confidence: 99%
“…BVAS is a universal standard to evaluate vasculitic activity, but its value as a predictor of mortality or relapse is controversial [18][19][20]. As for CY use, indications are different between Japanese guidelines [17] and British Society for Rheumatology (BSR)/British Health Professionals in Rheumatology (BHPR) guidelines [21].…”
Section: Discussionmentioning
confidence: 99%